Determination of Fraud Diamond Theory in Detecting Fraud in Financial Reporting - Wiraputra, Muhammad Rizki; Damayanti, Fera; Haryono (Research Horizon, 2025)
Financial statement fraud undermines transparency and accountability in state-owned enterprises, posing significant risks to stakeholders. This study aims to examine the effectiveness of the Fraud Diamond Theory, encompassing pressure, opportunity, rationalization, and capability, in detecting such fraud in Indonesian state-owned enterprises. The research analyzes 45 annual reports from 15 state-owned enterprises between 2021 and 2023, categorized into fraud and non-fraud groups, using logistic regression with 10 independent variables. Findings indicate that only the total accrual variable, representing rationalization, significantly influences fraud detection, while the other nine variables show no notable impact. This suggests that accounting manipulation through accruals is a critical factor in fraudulent financial reporting within state-owned enterprises. The study concludes that focusing on accrual-based indicators, rather than relying solely on external pressures or governance changes, enhances fraud detection. Strengthening internal audit procedures and monitoring accrual patterns are recommended to improve financial integrity. However, the study's focus on state-owned enterprises limits its generalizability, suggesting future research should include private companies and qualitative approaches to explore contextual factors.